Local Entropy and Lq-Dimensions of Measures in Doubling Metric Spaces - Anttila, Roope (The PUMP Journal of Undergraduate Research, 2020)
We define restricted entropy and Lq-dimensions of measures in doubling metric spaces and show that these definitions are consistent with the monotonicity of Lq-dimensions. This provides a correct proof for a theorem considering the relationships between local entropy and Lq-dimensions in a paper by Käenmäki, Rajala and Suomala, the original proof of which makes use of a slightly erroneous proposition.